Afforestation of Alluvial Waste Lands in the Nadia District (West Bengal) - Ray, P. K. (Indian Forester, 1956)
Nadia is one of the typical districts of the state of West Bengal where progressive deforestation and improper land use for centuries have led to a decline in the productive capacity of the soil, in many cases below the level of economic cultivation. Failure of timely rains and consequent crop failure is common. There is an acute scarcity of timber, fuel and fodder. The present article describes the afforestation of waste lands in the district undertaken by the Forest Department under the 5-Year Plans with a view to restore once again the much needed sylvan cover of the soil.